Posterior urethral valve in neonates - overview in a tertiary care center - Saravanan Natarajan,; Shankar Mohan, (Asian Journal of Medical Sciences, 2024)
Background: Posterior urethral valves are a unique obstructive pathology occurring in male children. Although known to present during various age groups when diagnosed in the neonatal period itself the outcome is better. Aims and Objectives: To study the incidence, clinical presentation, investigations, and management of neonates with posterior urethral valves and compare with literature. Materials and Methods: Retrospective study of neonates admitted to Government Mohan Kumaramangalam Medical College Hospital in South India for 1 year from August 2022 to July 2023. Results: Of a total of 16 cases studied the age of incidence of posterior urethral valve is 1–28 days with antenatally detected in nine cases. Fulguration was done in all 14 cases with vesicostomy in one case, bilateral ureterostomy in one case, and death in one case. Conclusion: Posterior urethral valve is a rare neonatal disease which is most often diagnosed antenatally. The investigations and modalities of management in our institution are inline with other studies in literature.